INDUKSI KALUS EMBRIOGENIK KELAPA SAWIT PADA MEDIA MS DENGAN PENAMBAHAN 2,4-D DAN AIR KELAPA MUDA - Titin Setyorini; Elisabeth Nanik Kristalisasi (AGROISTA : Jurnal Agroteknologi, 2019)
Embryogenic callus produced from somatic cells has a significant role in clonal propagation and oil palm breeding (assembly of superior varieties) through tissue culture techniques. Induction and development of embryogenic callus were determined by media composition, vitamins, amino acids, and growth regulators (hormones). This study aimed to determine the role of natural and synthetic hormone which supplemented in MS medium to induce embryogenic callus of oil palm. The research was conducted in laboratory of plant tissue culture, Stiper Agriculture Institute, Yogyakarta from February to May 2019. The explants were inoculated in solid MS medium with three treatments, namely MS medium (Murashige and Skoog), MS + synthetic hormone (2,4-Diclorophenoxyacetate), and MS + natural hormone (young coconut water). The results showed synthetic hormone (2,4-Diclorophenoxyacetate) which supplemented in MS medium can induce embryogenic callus of oil palm explants. However, natural hormone (coconut water) has not been able to induce embryogenic callus. Keywords: Callus induction, oil palm, 2,4-D, coconut water